Advances in Embryo Culture Systems - Smith, Gary D.; Monteiro da Rocha, Andre (Seminars in Reproductive Medicine, 2012)
The growth of mammalian embryos in the laboratory has progressed nicely over the last 60 to 70 years. This has been important for basic studies of preimplantation embryo regulation of growth, development, and differentiation. It has also been critical for the establishment of assisted reproductive technologies in the clinical setting to treat infertility. During the first 40 to 50 years, the primary focus was on defining soluble media components, which fortunately has yielded improved success in the culture of embryos. More recently, attention has shifted to other aspects of culture beyond media composition. In this review we discuss recent advances in preimplantation embryo culture that deal with modifying the insoluble culture environment, producing culture environments that are dynamic and not static, systems that allow more precise gas phase and/or media pH regulation/monitoring, and platforms that integrate with culture systems to allow analysis of embryos and thus assist in selection of the embryos with the greatest implantation potential.
Keywords: Embryo; culture; microenvironment; systems; equipment; analysis